2003
DOI: 10.1086/380389
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Changes in the Near-Infrared Spectrum of the Nova-like Variable V4332 Sagittarii

Abstract: We report on recent near-IR observations of V4332 Sgr -the nova-like variable that erupted in 1994. Its rapid, post-outburst evolution to a cool M type giant/supergiant, soon after its outburst, had showed that it was an unusual object differing from other eruptive variables like classical/symbiotic novae or born-again AGB stars. The present study of V4332 Sgr was motivated by the keen interest in the recent eruption of V838 Mon -an object with a spectacular light-echo and which, along with V4332 Sgr, is belie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 14 publications
2
46
1
Order By: Relevance
“…The 5 4 # 10 L , outburst luminosity of V4332 Sgr is difficult to estimate, as the distance d to the object is very uncertain. Using an estimate of pc (Martini et al 1999), we have shown that the star d p 300 has a quiescent luminosity of (Banerjee et al 2003). A 0.3 L , 9.5 mag brightening at outburst would yield an outburst luminosity of ∼ .…”
Section: Discussion: Is a Planetary Infall Responsible For The Outburmentioning
confidence: 96%
See 3 more Smart Citations
“…The 5 4 # 10 L , outburst luminosity of V4332 Sgr is difficult to estimate, as the distance d to the object is very uncertain. Using an estimate of pc (Martini et al 1999), we have shown that the star d p 300 has a quiescent luminosity of (Banerjee et al 2003). A 0.3 L , 9.5 mag brightening at outburst would yield an outburst luminosity of ∼ .…”
Section: Discussion: Is a Planetary Infall Responsible For The Outburmentioning
confidence: 96%
“…A considerable change in the spectral energy distribution (SED) of the object was seen between Two Micron All Sky Survey (2MASS) data of 1998 and observations in 2003 indicating the formation of a dust shell between these two epochs (Banerjee et al 2003). A better estimate of the epoch when the dust actually formed is discussed here.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…The mineralogical dust condensation sequence and processes involved are issues of considerable interest to astronomers. The AlO radical also received considerable attention after the strong detection of several A → X bands in the near-infrared (1-2.5 microns) in the eruptive variables V4332 Sgr and V838 Mon (Banerjee et al 2003;Evans et al 2003). Other IR detections of AlO include IRAS 08182-6000 and IRAS 18530+0817 (Walker et al 1997).…”
Section: Discussionmentioning
confidence: 99%